Investigation About Variation Law of Frost Heave Force of Seasonal Cold Region Tunnels: A Case Study - Zhang, Yuwei; Fan, Shengyuan; Yang, Donghui; Zhou, Fei (Frontiers in Earth Science, 2022)
The frost heave force (FHF) is one of the most important reason of inducing freezing damages of tunnel in seasonal frozen regions. Analyzing the change law of FHF is helpful to design for avoiding freezing damages in the tunnel lining. Field measurement is an approved method used in mechanical analysis of tunnel lining, however, it is difficult to measure the FHF directly, which is changed coupled with the original surrounding rock pressure (OSRP). In this paper, in order to clarifying the change law of the FHF, a new measuring method was presented. The best advantage of this method is that the FHF could be separated from the OSRP by measuring the surrounding rock temperature and the lining pressure at the same time. A lot of field measurement work about the FHF was conducted based on Jichoushan tunnel and the change law of the FHF was analyzed using the presented method. The results can provide preference for the antifreeze design of tunnel in seasonal cold regions.